2019
DOI: 10.1111/irv.12688
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, predictors, and performance of case definition—Interim results from the WHO global respiratory syncytial virus surveillance pilot

Abstract: Background: The lack of a uniform surveillance case definition poses a challenge to characterize the epidemiology, clinical features, and disease burden of the respiratory syncytial virus (RSV). Global standards for RSV surveillance will inform immunization policy when RSV vaccines become available. Methods: The WHO RSV surveillance pilot leverages the capacities of the Global Influenza Surveillance and Response System (GISRS). Hospitalized and non-hospitalized medically attended patients of any age were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
6
54
0
Order By: Relevance
“…These results are similar to those of other studies that confirm a significantly higher rate in children under 3 years of age (19.5%) compared to children over 3 years of age (5.6%) [ 47 ]. Even multicenter studies find that in children under 6 months the prevalence is 50% and in children under 2 years of age 88%, a fact that corroborates the high burden of RSV in children < 2 years, especially in infants < 6 months [ 50 , 51 ]. The younger the age, the greater the risk of RSV infection, as corroborated by several authors, indicating a greater risk especially in children between 3 to 5 months [ 48 , 52 , 53 ], although other studies point out that RSV-associated hospitalizations reach their maximum peak in children under 3 months [ 54 ].…”
Section: Discussionmentioning
confidence: 88%
“…These results are similar to those of other studies that confirm a significantly higher rate in children under 3 years of age (19.5%) compared to children over 3 years of age (5.6%) [ 47 ]. Even multicenter studies find that in children under 6 months the prevalence is 50% and in children under 2 years of age 88%, a fact that corroborates the high burden of RSV in children < 2 years, especially in infants < 6 months [ 50 , 51 ]. The younger the age, the greater the risk of RSV infection, as corroborated by several authors, indicating a greater risk especially in children between 3 to 5 months [ 48 , 52 , 53 ], although other studies point out that RSV-associated hospitalizations reach their maximum peak in children under 3 months [ 54 ].…”
Section: Discussionmentioning
confidence: 88%
“…[7][8][9]32 As declared by the World Health Organization RSV surveillance group-that leverages the capacities of the Global Influenza Surveillance and Response System-countries with existing influenza surveillance systems are able to build on RSV surveillance on top of their influenza surveillance program. 39 However, the lack of a uniform case definition for RSV still poses a challenge to characterize the epidemiology, clinical features, and disease burden of RSV, thus complicating the interpretation of surveillance results. 39 In our study, the standard case definition of ILI proposed by the European Centre for Disease Prevention and Control, 14 which includes an abrupt onset of fever (>38°C) or feverishness, was used, as also suggested by others 12,13 ; however, it has been shown that including fever in a case definition for RSV may lower the sensitivity to detect cases.…”
Section: Discussionmentioning
confidence: 99%
“…39 In our study, the standard case definition of ILI proposed by the European Centre for Disease Prevention and Control, 14 which includes an abrupt onset of fever (>38°C) or feverishness, was used, as also suggested by others 12,13 ; however, it has been shown that including fever in a case definition for RSV may lower the sensitivity to detect cases. 13,39 This means that, in interpreting our results, the RSV burden should have been underestimated. In addition, another limitation of our study is that sampling time was restricted to influenza season, thus the prevalence of RSV was estimated only in the period spanning from November to April.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted January 22, 2021. ; https://doi.org/10.1101/2021.01.13.20202200 doi: medRxiv preprint 8 precedes that of influenza viruses in Western Europe [11]. Though RSV, hMPV, coronaviruses and other NIRVs do not strictly follow the same pattern as influenza viruses [13], many tend to also circulate during the winter season in temperate regions, thus making influenza surveillance a relevant system for their study [14,15].…”
Section: Discussionmentioning
confidence: 99%